Mycotoxin binders potential on histological of ovary mice exposed by zearalenone - Abdul Samik; Erma Safitri (Veterinary World, 2017)
Aim: This study was conducted to examine the potential of mycotoxin binder in ceasing zearalenone (ZEN) effect on mice reproduction. ZEN mycotoxin can induce reactive oxygen species that may cause damage and cell death. ZEN is estrogenic so that it may affect the reproductive organs failure.